Predicting the risk of bleeding during dual antiplatelet therapy after acute coronary syndromes. Issue 15 (5th April 2017) - Alfredsson, Joakim; Neely, Benjamin; Neely, Megan L; Bhatt, Deepak L; Goodman, Shaun G; Tricoci, Pierluigi; Mahaffey, Kenneth W; Cornel, Jan H; White, Harvey D; Fox, Keith AA; Prabhakaran, Dorairaj; Winters, Kenneth J; et al.
Abstract : Objectives: Dual antiplatelet therapy (DAPT) with aspirin + a P2Y12 inhibitor is recommended for at least 12 months for patients with acute coronary syndrome (ACS), with shorter durations considered for patients with increased bleeding risk. However, there are no decision support tools available to predict an individual patient's bleeding risk during DAPT treatment in the post-ACS setting. Methods: To develop a longitudinal bleeding risk prediction model, we analy sed 9240 patients with unstable angina/non-ST segment elevation myocardial infarction (NSTEMI) from the Targeted Platelet Inhibition to Clarify the Optimal Strategy to Medically Manage Acute Coronary Syndromes (TRILOGY ACS) trial, who were managed without revasculari sation and treated with DAPT for a median of 14.8 months. Results: We identified 10 significant baseline predictors of non-coronary artery bypass grafting (CABG)-related Global Use of Strategies to Open Occluded Arteries (GUSTO) severe/life-threatening/moderate bleeding: age, sex, weight, NSTEMI (vs unstable angina), angiography performed before randomi sation, prior peptic ulcer disease, creatinine, systolic blood pressure, haemoglobin and treatment with beta-blocker. The five significant baseline predictors of Thrombolysis In Myocardial Infarction (TIMI) major or minor bleeding included age, sex, angiography performed before randomi sation, creatinine and haemoglobin. The models showed good predictive accuracy with Therneau's C- indices: 0.78 (SE = 0.024) for the GUSTO model and 0.67 (SE = 0.023) for the TIMI model. Internal validation with bootstrapping gave similar C -indices of 0.77 and 0.65, respectively. External validation demonstrated an attenuated C -index for the GUSTO model (0.69) but not the TIMI model (0.68). Conclusions: Longitudinal bleeding risks during treatment with DAPT in patients with ACS can be reliably predicted using selected baseline characteristics. The TRILOGY ACS bleeding models can inform risk –benefit considerations regarding the duration of DAPT following ACS. Trial registration: ClinicalTrials.gov identifier: https://clinicaltrials.gov/ct2/show/NCT00699998